Hirayama Disease: a Case Report with Late Onset - Albuquerque, Antônio Marco Duarte de; Ferreira, Sarah Câmara; Silva, Sophia Alves de França; Melo, Rodrigo Araújo de (Brazilian Journal of Case Reports, 2024)
The etiology of Hirayama's disease (HD) is still controversial, but the most accepted mechanism is the repetition of sudden neck flexion movements, which causes a flattening of the cervical spinal cord. It reaches the cells of the anterior tip of the medulla in the C7-T1 segments. 45-year-old patient with HD, diagnosed 1 year ago with typical atrophy of the left upper limb (LUL) associated with fasciculation and decreased osteotendinous reflexes in upper limbs (ULL). Due to the rarity of the disease, there are many underdiagnosed cases, which results in low epidemiological data reported. We are aware that the prevalence in males is explained by accelerated growth at puberty.